(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Ukrainian Orthodox Church between the war and spiritual revival. The Church and the World Crisis.The war that today saddens the entire humanity started from the ambition of a great military and economic power, Russia, which for three decades does not accept the idea that the Ukrainian people are not identical with the Russian people and that Ukraine is another state that wants to build its own way into history. A similar phenomenon happened years ago through the tragic war in the Balkans, when Serbia could not accept the independence of the Kosovo region and the idea that another people lived there with their own ambitions. The Russian-Ukrainian war has a major impact on the lives of Orthodox believers around the world. We see clerics who bless war and incite hatred towards brothers of the same faith, who have turned into tools of an aggressor state and believe political illusions that have nothing to do with the love of the Savior Jesus Christ. In this study I present the historical events that led to the tragic inter-Orthodox war.